Tinker Bell and the legend of the NeverBeast [videorecording (DVD)] (Disney DVD., 2015)
Fun and talented animal fairy Fawn believes you can't judge a book by its cover, or an animal by its fangs, so she befriends a huge and mysterious creature known as the NeverBeast. While Tinkerbell and her friends aren't so sure about this scary addition to Pixie Hollow, the elite Scout Fairies set out to capture the monster before he destroys their home. Fawn must trust her heart and take a leap of faith if she hopes to rally the girls to save the NeverBeast.